In silico Identification of Drug Analogues for Antifertility - Shukla, Shriddha; Dixit, Savita; Pardasani, K.R. (Asian Journal of Chemistry, 2012)
The identification of new, clinically relevant, molecular targets is of utmost importance for the discovery of innovative drugs. In this paper natural products (plant species) are selected for comparative study in order to analyze the compounds showing antifertility property with respect to the metabolic pathways involved. The two enzymes are identified as targets namely, L-aspartate dehydrogenase (EC 1.4.1.21) and trans-hexaprenyl-trans-transferase (EC No. 2.5.1.30) from nicotinate and nicotinamide metabolism and biosynthesis of steroids respectively. It has been found that there are no inhibitors existing for these enzymes so it becomes necessary to identify and design the new inhibitors. Further in order to design and model the analogues on screening various libraries we have identified most potent ligands using auto-dock. The most appropriate inhibitors for the targets in terms of binding affinity and enzyme inhibition constant (Ki) have been identified.